Biofilm Formation and Detection of Fluoroquinolone- and Carbapenem-Resistant Genes in Multidrug-Resistant Acinetobacter baumannii - María-Guadalupe Avila-Novoa; Oscar-Alberto Solís-Velázquez; Daniel-Eduardo Rangel-López; Jean-Pierre González-Gómez; Pedro-Javier Guerrero-Medina; Melesio Gutiérrez-Lomelí (Canadian Journal of Infectious Diseases and Medical Microbiology)
Acinetobacter baumannii is an important opportunistic pathogen that shows resistance to cephalosporins, penicillins, carbapenems, fluoroquinolones, and aminoglycosides, the multiresistance being associated with its ability to form biofilms in clinical environments. The aim of this study was to determine biofilm formation and its potential association with genes involved in antibiotic resistance mechanisms of A. baumannii isolates of different clinical specimens. We demonstrated 100% of the A. baumannii isolates examined to be multidrug resistant (MDR), presenting a 73.3% susceptibility to cefepime and a 53.3% susceptibility to ciprofloxacin. All A. baumannii isolates were positive for blaOXA-51, 33.3% being positive for blaOXA-23 and ISAba1, and 73.3% being positive for gyrA. We found 86.6% of A. baumannii strains to be low-grade biofilm formers and 13.3% to be biofilm negative; culturing on Congo red agar (CRA) plates revealed that 73.3% of the A. baumannii isolates to be biofilm producers, while 26.6% were not. These properties, combined with the role of A. baumannii as a nosocomial pathogen, increase the probability of A. baumannii causing nosocomial infections and outbreaks as a complication during therapeutic treatments and emphasize the need to control A. baumannii biofilms in hospital environments.